The Relationship Between Islamic Law and Positive Law of Indonesia and Recht Customs - Bustomi, Achmad (Jurnal Legisci, 2024)
The relationship between Islamic law, Indonesia's Positive Law, and customary law so far, when viewed in terms of implementation, sometimes has not been found, but nevertheless, the law of the potion has become a measure of national law for the citizens of the community, including Muslims or cultures in the territory of Indonesia. The formation of positive law is primarily influenced by the values contained in the teachings of Islam so that several regulations are legitimized in the Indonesian legal system, including marriage law, waqf, and hajj, as well as some customary laws included in the compilation of Islamic law and Indonesia legal system. This study uses a literature research method that approaches the supporting books in this paper. It is hoped that the synergy of the three legal systems can continue to harmonize as a form of diversity and create harmony between citizens. The result of this research was The correlation between Islamic law, Indonesia's positive law, and customary law, and shows how these three legal systems interact and influence each other. Harmonious integration between these three legal systems is important to create a fair and effective legal system in Indonesia.